Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2008
DOI: 10.1007/s10620-008-0444-2
|View full text |Cite
|
Sign up to set email alerts
|

Synaptic Plasticity: The New Explanation of Visceral Hypersensitivity in Rats with Trichinella spiralis Infection?

Abstract: Synaptic plasticity was observed in SD rats infected by Trichinella spiralis and was associated with visceral sensitivity, which suggests that it may play an important role in the formation of visceral hypersensitivity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
18
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 24 publications
(22 citation statements)
references
References 55 publications
3
18
0
Order By: Relevance
“…35 Several studies are now providing initial evidence suggesting the involvement of neuroplastic changes in the enteric nervous system or afferent pathways in functional gastrointestinal disorders, including IBS. 35,39 Infiltration of MCs in the colonic mucosa of patients with IBS promote neuronal sprouting and neuroplastic changes owing to the release of nerve growth factor. 40 Nerve growth factor acting on tropomyosin receptor kinase A (TrkA) receptors could also up-regulate of TRPV1 expression.…”
Section: Mast Cells Modulate Visceral Sensationmentioning
confidence: 99%
“…35 Several studies are now providing initial evidence suggesting the involvement of neuroplastic changes in the enteric nervous system or afferent pathways in functional gastrointestinal disorders, including IBS. 35,39 Infiltration of MCs in the colonic mucosa of patients with IBS promote neuronal sprouting and neuroplastic changes owing to the release of nerve growth factor. 40 Nerve growth factor acting on tropomyosin receptor kinase A (TrkA) receptors could also up-regulate of TRPV1 expression.…”
Section: Mast Cells Modulate Visceral Sensationmentioning
confidence: 99%
“…TEM was performed as previously described with some modifications . In brief, IEC‐18 cells were fixed with 2.5% phosphate‐buffered glutaraldehyde for 2 h and stored at 4°C until embedding.…”
Section: Methodsmentioning
confidence: 99%
“…For example, we found that synaptic plasticity in ENS of PI-IBS model rats infected with Trichinella spiralisis associated with visceral sensitivity. 7 Dorsal root ganglia neuron excitability was increased significantly in the PI-IBS model. 11 Others showed through functional magnetic imaging and positron emission tomography studies that brain areas involved in visceral sensation processing, such as the prefrontal cortex and cingulate cortex, were activated abnormally in IBS patients.…”
Section: Introductionmentioning
confidence: 93%
“…3 The possible mechanisms of PI-IBS include mucosal injury and inflammation, 4 increased intestinal permeability, 5 mast cell hyperplasia, 6 and enteric nerve alteration. 7,8 Abdominal pain is the most predominant and distressing symptom of PI-IBS. 9 Visceral hypersensitivity, which is generally considered to be a hallmark of IBS with lowered thresholds for pain and increased intensity of sensations, was responsible for the symptom.…”
Section: Introductionmentioning
confidence: 99%